2020
DOI: 10.1002/ijgo.13289
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 lockdown on admission to gynecological emergency departments: Results from a multicenter Italian study

Abstract: Objective To evaluate the impact of the COVID‐19 lockdown on admissions to gynecological emergency departments (ED) of three Italian university hospitals with different rates of COVID‐19 incidence. Methods A retrospective study was conducted in the gynecological EDs of Modena (Emilia‐Romagna), Sassari and Cagliari (Sardinia) regarding all admissions to gynecological EDs during November 1 to 30, 2019, and March 11 to April 9, 2020 (lockdown period). Results A total of 691 women (mean age 38.3 ± 14.3 years) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 9 publications
3
22
1
2
Order By: Relevance
“…Focusing on hygiene, decreased social interaction, and working remotely are all behavioral modifications followed by pregnant women during the lockdown period as declared by Philip et al 10 We found a drastic decrease in the emergency department visits during the pandemic where no restrictions were imposed on the patient's basic right to seek medical attention in the emergency department for urgent health problems. Similar findings were reported in Italy by Grandi et al 11 Moreover, there was a decrease in hospitalization rate compared to pre-lockdown period. This was also seen in India where Kumari et al mentioned a reduction in hospitalization by 43% in their country during the lockdown.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Focusing on hygiene, decreased social interaction, and working remotely are all behavioral modifications followed by pregnant women during the lockdown period as declared by Philip et al 10 We found a drastic decrease in the emergency department visits during the pandemic where no restrictions were imposed on the patient's basic right to seek medical attention in the emergency department for urgent health problems. Similar findings were reported in Italy by Grandi et al 11 Moreover, there was a decrease in hospitalization rate compared to pre-lockdown period. This was also seen in India where Kumari et al mentioned a reduction in hospitalization by 43% in their country during the lockdown.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, many patients might be avoiding hospital visits and admissions and prefer treatment on an outpatient setting, minimizing by that the risk of COVID-19 infection. 11 Surprisingly, in our study, fetal complications and NICU admission were found to be significantly higher before the lockdown. We also did not note any significant change in the cesarean rate.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Several studies have been conducted to address non-COVID disease referrals during the COVID-19 era. However, few studies have examined only gynecology admissions [ 10 14 ]. The number of admissions in three Italian hospitals for gynecological emergencies has decreased significantly due to the COVID-19 lockdown [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined only gynecology admissions [ 10 14 ]. The number of admissions in three Italian hospitals for gynecological emergencies has decreased significantly due to the COVID-19 lockdown [ 10 ]. Furthermore, Frey et al reported that about 38% of women experienced cancellation, postponing, or modification in their scheduled gynecologic oncology care due to COVID-19 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%